Biodiversitas Lipas Dan Penerapan Biosekuriti Pada Rumah Sakit Umum Daerah Dan Swasta Di Kota Kendari Sulawesi Tenggara: Cockroach Biodiversity and the Application of Biosecurity in Regional and Private Public Hospitals in Kendari City, Southeast Sulawesi - Nirwan, Muhammad; Rafiuddin, Ari Tjahyadi; Amraeni, Yunita (Perkumpulan Entomologi Kesehatan Indonesia, 2024)
Cockroaches play a role in the transmission and spread of human pathogens in the hospital environment. Cockroaches are home to pathogenic organisms and are able to move freely in the hospital environment. Biosecurity in hospitals is very important to prevent the spread of infectious diseases and maintain a safe environment for patients and health workers. The implementation of biosecurity is often ignored or inconsistent in several hospitals, both in regional public hospitals and private hospitals, especially in areas such as Kendari City, Southeast Sulawesi. This study aims to identify and analyze the biodiversity of cockroaches and evaluate the implementation of biosecurity in regional public hospitals and private hospitals in Kendari City. The type of research is analytical descriptive research and has been carried out at the Regional Public Hospital and Private Hospital in Kendari City, from August 13 to September 10, 2023. The types of cockroaches found in the Regional Public Hospital and Private Hospital in Kendari City are Periplaneta americana and Blattella germanica. The distribution of cockroaches in the Regional Public Hospital was higher than in Private Hospitals in Kendari City. P. americana and B. germanica cockroaches in both public and private hospitals were mostly found at the wastewater observation point, followed by inpatient and kitchen. P. americana and B. germanica infestations were in the low category in both public and private hospitals. The implementation of personal and workplace biosecurity in private hospitals was better than in public hospitals, while environmental biosecurity in both public and private hospitals had equally good implementation.